(3fSNI GdMbs - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s
(3ChdgG (B:s
(3aj GhdgG GfgG bQFJ(B: (3Ydi GdeDdaaj GdYTQ GdChd ef Pj GdMLI (B621(3g`, haj BNQ fU GdbQGAI cJGHI JajO Cf GdbQGAI MUdJ YdgG Jchf cJGHI eMj GdOjf GdOjf faSgs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs